2020
DOI: 10.26389/ajsrp.l071219
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Online Buying Behavior of Customers in Saudi Arabia: العوامل المؤثرة على سلوك المستهلك عند التسوق عبر الإنترنت في السعودية

Abstract: Recent years witnessed the establishment of many Saudi online stores; the accessibility of such online stores provides online shopping facilities that will increase online shopping in KSA. Therefore, it becomes highly important to study and understand the different factors that affect consumers’ behavior towards online buying in Saudi Arabia based on the fact that e-commerce has been one of the strategic objectives that support fulfilling the Saudi Vision 2030. The purpose of this study is to identify factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The concept of customer behavior is one of the important topics that attracted the attention of many studies in various scientific fields because of its great and effective impact on safe banks. The decisions of the investigated banks because it directly affects their profits (Baabdullah & Ansari, 2020) [6] , What is the concept of customer behavior as "that behavior that the customer shows in searching for the purchase or use of banking services, ideas or experiences that he expects will satisfy his desires or needs, according to the available heritage capabilities (Kotler & Keller, 2011) [13] ,…”
Section: The Concept Customer Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of customer behavior is one of the important topics that attracted the attention of many studies in various scientific fields because of its great and effective impact on safe banks. The decisions of the investigated banks because it directly affects their profits (Baabdullah & Ansari, 2020) [6] , What is the concept of customer behavior as "that behavior that the customer shows in searching for the purchase or use of banking services, ideas or experiences that he expects will satisfy his desires or needs, according to the available heritage capabilities (Kotler & Keller, 2011) [13] ,…”
Section: The Concept Customer Behaviormentioning
confidence: 99%
“…The results of the statistical analysis of this dimension as presented in table (6) revealed that the variable amounted to 10 the lowest accounting circles at 2.01 and a standard deviation (1.024), expressed by the question "Bank management is careful to make changes in order to conform to its creative process and the continuous adaptation of change to market and customer requirements".The most positive contribution to this component in the middle of my account is "banking efforts to develop regularly renewed ideas and deliver significant and helpful innovation according to the customer's desires." (4.10), the overall dimension is 3.38, and as a consequence, private banks are interested in the availability of training and learning programs for their employees to gain the information and skills they need to accomplish their tasks.…”
Section: -After Learningmentioning
confidence: 99%